Pola Pemilihan Bahasa Masyarakat Ranah Keluarga Kota Bandung - Trianto, Ikmal; Arianingsih, Anisa (GERAM, 2025)
This study examines the phenomenon of code-mixing in language use in family interactions, both face-to-face and online, in Bandung. The study uses a descriptive qualitative approach with data collection methods in the form of questionnaires distributed via WhatsApp messages and interviews. The results show that the dominant language used in family communication is a mixed language (Sundanese-Indonesian) with a percentage of 58.73%. The use of Indonesian is 26.19%, Sundanese is 15.08%, and English/foreign languages is only 0.57%. Mixed language is more widely used in daily communication, both within and outside the family. Code-mixing and code-switching are common phenomena in social interactions among multilingual communities in Bandung. In addition to the presence of virtual and face-to-face communication spaces that refer to language use, code-mixing and code-switching are also influenced by factors such as psychological, educational, and linguistic factors. This phenomenon not only reflects language habits but also the complexity of human interactions in multilingual societies.